Excel-Based Financial Report Preparation Training for Pharmacy Entrepreneurs Who Are Members of HISFARMA in the Special Region of Yogyakarta - Nugraeni; Utomo, Rochmad Bayu; Pertiwi, Ni Luh Gde Ana (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This activity aimed to assist pharmacy owners, members of HISFARMA in Yogyakarta, who struggled with manual financial reporting. The goal was to improve their skills in preparing financial reports using Excel. Method: A training program was conducted involving 30 HISFARMA member pharmacies. Participants were taught to prepare financial reports using Excel through practical exercises and direct mentoring. Practical Application: The training provided pharmacy owners with practical skills to organize financial data efficiently, streamline reporting processes, and enhance cost classification, leading to better financial management. Conclusion: After the training, participants showed significant improvement, particularly in the classification of the expenses. Using Excel contributed to more accurate and professional financial reporting among HISFARMA pharmacy owners.